COVID‐19 did not result in increased hospitalization for stroke and transient ischemic attack: A nationwide study. (21st April 2022) - Simonsen, Claus Z.; Blauenfeldt, Rolf A.; Hedegaard, Jakob N.; Kruuse, Christina; Gaist, David; Wienecke, Troels; Modrau, Boris; Johnsen, Søren P.; Andersen, Grethe
Abstract: Background: The risk of thrombosis increases in infectious diseases, yet observational studies from single centers have shown a decrease in admission of acute ischemic stroke patients during the COVID‐19 pandemic. To investigate unselected stroke admission rates we performed a nationwide study in Denmark. Methods: We extracted information from Danish national health registries. The following mutually exclusive time periods were compared to the year before the lockdown: (1) first national lockdown, (2) gradual reopening, (3) few restrictions, (4) regional lockdown, and (5) second national lockdown. Results: Generally, admission rates were unchanged during the pandemic. In the unadjusted data, we observed a small decrease in the admission rate for all strokes under the first lockdown (incidence rate ratio: 0.93, confidence interval [CI]: 0.87–0.99) and a slight increase during the periods with gradual reopening, few restrictions, and the regional lockdown driven by ischemic strokes. We found no change in the rate of severe strokes, mild strokes, or 30‐day mortality. An exception was the higher mortality for all strokes during the first lockdown (risk ratio: crude 1.30 [CI: 1.03–1.59]; adjusted 1.17 [CI: 0.93–1.47]). The quality of care remained unchanged. Conclusion: Stroke admission rates remained largely unchanged during the pandemic, while an increased short‐term mortality rate in patients admitted with stroke observed during the first lockdown was seen, probably reflecting that the more frail patients constituted a higher proportion of admitted patients at the beginning of the pandemic. Abstract : The rate of stroke admissions during the COVID‐19 pandemic remained largely unchanged in Denmark. Higher mortality was only seen in the first period. Quality of treatment remained unchanged.